SOFT LINING OF IMMEDIATE COMPLETE DENTURES: CASE REPORT - Džaferović, Jasmin; Maletin, Aleksandra; Jeremić Knežević, Milica; Đurović Koprivica, Daniela (Sanamed, 2024)
Introduction: With the placement of dental implants in edentulous patients, creating and adapting immediate dentures is crucial to allow patients to perform basic physiological functions during the osseointegration period without affecting implant healing. This report presents a case of direct soft lining of immediate complete dentures following implant placement. Case Report: Six dental implants were inserted in the upper jaw, while the patient retained natural teeth in the lower jaw. An immediate complete denture was fabricated and adjusted for the upper jaw. The prosthesis base was prepared and processed to accommodate soft lining material. Adhesive was applied to the prepared base, followed by silicone application for soft fitting onto the prosthesis base, which was then inserted into the patient’s mouth. After three minutes, the denture was removed, and soft lining treatment of the immediate complete denture was completed. Conclusion: Direct soft lining facilitated patient adaptation to the immediate prosthesis and supported safer healing and osseointegration until definitive work could be completed. The addition of a soft silicone layer reduced pressure on the residual alveolar ridge and improved adhesion of the immediate prosthesis.